'In a rush': Time-space compression and its impacts on cruise excursions. (December 2019) - Gutberlet, Manuela
With the increase in large-scale cruise tourism worldwide, researchers have highlighted the inauthenticity of the cruise experience and the reconstruction of space. This research deals with new aspects: fast tourism through time-space compression, and the formation of enclosed, customized 'tourist bubbles' that confine the tourists and promote a constructed authenticity of the experience on-shore. The second aim is to advance applied research in slower cruise excursions, especially in emerging cruise destinations. The research is based on extensive field work conducted during nine cruise-excursions to the sand desert and an oasis in the Sultanate of Oman. Oman is in the early stages of developing mega-cruise tourism while having received little attention in tourism research. For this study, in-depth interviews were conducted with German-speaking cruise tourists, cruise employees as well as with local cultural brokers and the Minister of Tourism. Moreover, participant observation, travel ethnography and photography were applied. Results indicate while moving from one customized 'tourist bubble' to the next one, time is controlled and enhanced through fast modes of transportation and a tight schedule of the excursion. The tourists and their cultural brokers are 'contained' in time and space, while some are struggling for more authentic experiences. They are shielded off from the local environment, 'grazing' destinations within a short time.